Previus study on sweet sorghum foliar diagnosis - Rosolem, C.A.; Malavolta, E. (Pesquisa Agropecuaria Brasileira, 2014)
Good results have been obtained when a sample of one leaf of medium height of the plant at boot stage is used for foliar diagnosis of grain sorghum. In this work the same technique was tested for two sweet sorghum cultivars (Brandes and Rio), grown in two soils ("Latossolo Roxo" and Dark-Red Latosol), under three N, P and K levels, and grown in greenhouse, with Hoagland and Arnon full strength solution, the same diluted 5 and 10 fold. In the greenhouse the following nutrient levels at boot stage could be considered as adequate: 3.2% of N. 0.80 to 0.95% of P, 2.60 to 3.10% of K, 0.45 to 0.65% of Ca, 0.45 to 0.52% of Mg, 9 to l0 ppm of Cu and 48 to 54 ppm of Mn. The sampling utilized did not show sufficient sensitivity to detect differences among the treatments under field conditions; it was adequate however, in experiments in the greenhouse wherein there were large differences in the level of nutrient in the substrate.